2018
DOI: 10.1007/s00417-017-3891-7
|View full text |Cite
|
Sign up to set email alerts
|

QUIET PLEASE! Effect of distraction on simulated posterior segment surgical performance

Abstract: Purpose To determine the effect of distraction on posterior segment surgical performance using a virtual reality simulator in expert and novice ophthalmic surgeons. Methods Twenty subjects were given 6 min to read an unpublished research paper and then were randomized into two groups. Group 1 subjects were allowed 3 min to complete a standardized vitreoretinal simulated task undistracted. Group 2 subjects were asked six questions on the research paper whilst completing the same task. Each subject then performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Contrary to the previous finding on the effect of auditory distraction on simulated posterior segment surgery performance (McGowan et al. ), the total operation time was not affected in this study. It is interesting to note that in contrast to what was expected, the operation time decreased in most modules.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the previous finding on the effect of auditory distraction on simulated posterior segment surgery performance (McGowan et al. ), the total operation time was not affected in this study. It is interesting to note that in contrast to what was expected, the operation time decreased in most modules.…”
Section: Discussioncontrasting
confidence: 99%
“…It showed no reduction in surgical score, but it significantly affected the efficiency of the surgeon, leading to slower surgery (McGowan et al. ). Also on simulated anterior segment surgery, the effect of distraction has been evaluated for both expert and novice ophthalmic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent acoustic and visual alarms from patient monitoring lead to alarm fatigue. Correct alerts are no longer perceived because the practitioner becomes dulled [34][35][36][37][38][39][40]. Distractions, such as background music, alarm sounds, and other cognitive and emotional stimuli, are ubiquitous in operating rooms and intensive care units and cause attention consumption, which reduces the cognitive capacity of care providers for the complex task of patient monitoring [41].…”
Section: Patient Monitoring In Clinical Realitymentioning
confidence: 99%
“…These results revealed the importance of avoiding unnecessary distractions in the operating room as much as possible, while providing care providers with the simplest-to-interpret monitoring possible. The benefits of avatar-based patient monitoring may be especially helpful in high-workload situations when cognitive resources and task performance are reduced [40,[55][56][57].…”
Section: Distractionsmentioning
confidence: 99%
“…[4,9] Several experiments have shown that distractions reduce performance during tasks and increase perceived stress levels and workload. [9][10][11][12][13] Patient monitoring occurs at the critical interface between the physical quantities measured in the patient and the sensorium and cognition of the human decisionmakers. [6,8,14] Previous research has found that state-of-the-art patient monitoring shows deficits in information transfer due to its design.…”
Section: Co2mentioning
confidence: 99%